Preparation and Characterization of BSA-loaded Chitosan Microspheres - Hendradi, Esti; Sari, Retno; Anggai, Rifka Anggraini (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
=